If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x(5x + 2) = 0 Reorder the terms: 3x(2 + 5x) = 0 (2 * 3x + 5x * 3x) = 0 (6x + 15x2) = 0 Solving 6x + 15x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3x'. 3x(2 + 5x) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(2 + 5x)' equal to zero and attempt to solve: Simplifying 2 + 5x = 0 Solving 2 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 0 + -2 5x = 0 + -2 Combine like terms: 0 + -2 = -2 5x = -2 Divide each side by '5'. x = -0.4 Simplifying x = -0.4Solution
x = {0, -0.4}
| f-4-3=-2 | | =3(2x-30) | | f-4-3=2 | | (M+5)+1.5=2 | | .44*7=x | | 15x+29(x-2)=294 | | o=v+1 | | 6x-24=-2x+32 | | (Y-4)+8=6 | | C+c=1 | | 6x-(24)=-2x+32 | | 6/4a+8+9/6a+12 | | 36.6y=256.2 | | 2log[3]+log[3]5=log[3](14x+3) | | (6x^5)(6)= | | (8x-16)=(4x+20) | | 16+5=15x | | d-2+5=-13 | | o+7=-3 | | 6b+18=8b-16 | | d-2+5=13 | | (X-1)+5=2 | | 6y-2+2=14 | | r^2+17+52=0 | | -3(5g+1)-6=-9 | | log[3]+log[3]5=log[3](14x+3) | | 6x-(3x+8)=5x-(4-6x) | | 8k+12-2=6 | | (8x-16)+(4x+20)= | | -4(5y-7)+3(2y+8)= | | u^2+16u+36=0 | | (4a^3+a-8)-(7-8a^3+3a^2)= |